Resolving Disputes over Frozen Embryos - Robertson, John A. (The Hastings Center report, 1989)
The relation between respect for family and reproductive choice and use of IVF technology is in dispute in recent legal cases on the disposition of frozen embryos. Couples in IVF programs should be encouraged to stipulate in advance binding instructions regarding the disposition of such embryos.